New Varieties of English - Suwarni Wijaya Halim (Journal of English Language and Culture, 2017)
In the past, English was used as a mean of communication by people living in the United Kingdom, the United States, and Australia only. However, nowadays, different kinds of “Englishes” have emerged in many different countries. Some interesting phenomenon of English varieties can be found in Asia. The usage of English in Asia is blended with the characteristics of the countries’ native languages, which results in English with different pronunciation, vocabularies, grammar, and so on. In this paper, the writer will discuss the emerging English varieties in countries located in south-east of Asia. In addition, the possibility for the emergence of Indonesian English will also be discussed in this paper. Keywords: English varieties, English in Asia, World Englishes